Dimensions for hearing-impaired mobile application usability model - Nathan, Shelena Soosay; Hussain, Azham; Hashim, Nor Laily; Omar, Mohd Adan (IP Publishing LLC, 2017)
This paper discuss on the dimensions that has been derived for the hearing-impaired mobile applications usability model. General usability model consist of general dimension for evaluating mobile application however requirements for the hearing-impaired are overlooked and often scanted. This led towards mobile application developed for the hearing-impaired are left unused. It is also apparent that these usability models do not consider accessibility dimensions according to the requirement of the special users. This complicates the work of usability practitioners as well as academician that practices research usability when application are developed for the specific user needs. To overcome this issue, dimension chosen for the hearing-impaired are ensured to be align with the real need of the hearing-impaired mobile application. Besides literature studies, requirements for the hearing-impaired mobile application have been identified through interview conducted with hearing-impaired mobile application users that were recorded as video outputs and analyzed using Nvivo. Finally total of 6 out of 15 dimensions gathered are chosen for the proposed model and presented.